Sintomas de dist??rbios osteomusculares relacionados ?? atividade de cirurgi??es-dentistas brasileiros - Bachiega, Joanna Carolina (2009)
Work-related musculoskeletal disorders (MSDs) are characterized by the occurrence of symptoms linked either directly or indirectly to professional practice. MSDs are a combination of an overload on the musculoskeletal system and a lack of time for recovery. Dentists are exposed to a number of factors related to MSDs. The aim of the present study was to describe the frequency of musculoskeletal symptoms and factors associated to work-related MSDs in a sample of Brazilian dentists. A descriptive study was carried out on a convenience sample of 100 dentists (71 women and 29 men) in the public healthcare system in the city of S??o Bernardo do Campo (Brazil), using the Nordic Musculoskeletal Questionnaire, which identifies the affected part of the body and potential relations to work. Frequencies and percentages were calculated for affected regions, work preformed, demographic data and activities, also considering possible associations between region of the body and gender, marital status, schooling, working hours, age group, years of work and specialties, using the chi-square test and Fisher s exact test. Pain complaints were concentrated in the cervical region (67%), lumbar region (61%), wrists/hands/fingers (47%) and shoulders (38%). The specialties that were most associated with symptoms were pediatric dentistry (neck and shoulders). The general dentistry had the regions of neck and wrists. The present study revealed a high frequency of work-related pain symptoms, especially among the pediatric and general dentistry specialties